Perbandingan Range of Movement pada Pasien Post Total Knee Replacement Teknik Cruciate Retaining dengan Teknik Posterior Stabilized - Arikalang, Patrick S.; Noersasongko, Albertus D.; Suharso, Tommy (Universitas Sam Ratulangi, 2025)
Abstract: Total knee replacement (TKR) is a common surgical procedure to treat pain and dysfunction in the knee joint due to osteoarthritis. Two techniques that are often used are cruciate retaining (CR) and posterior stabilized (PS). This study aimed to compare the range of movement (ROM) between the two techniques. This was a comparative study with prospective cohort design conducted at Prof. Dr. R. D. Kandou Manado Hospital. A total of 100 patients undergoing TKR were included, consisting of 12 patients with CR technique and 88 patients with knee PS. ROM technique was measured using goniometer. Statistical analysis used the Mann-Whitney test and linear regression. The results showed that the median age of patients was 66 years dominated by women (77%). There were no significant differences in ROM of knee flexion and extension between CR and PS techniques (p>0.05). Regression analysis showed that the PS technique tended to have a lower ROM than CR (6-7° for knee flexion), but statistically meaningless. The patient's age had a meaningful negative relationship with post-TKR ROM. In conclusion, the CR and PS techniques provide equivalent ROM results in post-TKR patients. The selection of techniques can be adjusted to the operator's expertise, the availability of implants, and hospital facilities. Follow-up research with longer duration and multi-flashlights is needed to evaluate long-term outcomes. Abstrak: Total knee replacement (TKR) merupakan prosedur bedah yang umum dilakukan untuk mengatasi nyeri dan disfungsi pada sendi lutut akibat osteoartritis. Dua teknik yang sering digunakan yaitu cruciate retaining (CR) dan posterior stabilized (PS). Penelitian ini bertujuan membandingkan range of movement (ROM) antara kedua teknik tersebut. Penelitian ini merupakan studi komparatif dengan desain kohort prospektif yang dilakukan di RSUP Prof. Dr. R. D. Kandou Manado. Sebanyak 100 pasien yang menjalani TKR diikutsertakan, terdiri dari 12 pasien dengan teknik CR dan 88 pasien dengan teknik PS. ROM lutut diukur menggunakan goniometer. Analisis statistik menggunakan uji Mann-Whitney dan regresi linear. Hasil penelitian memperlihatkan median usia pasien ialah 66 tahun didominasi perempuan (77%). Tidak terdapat perbedaan bermakna pada ROM fleksi dan ekstensi lutut antara teknik CR dan PS (p>0,05). Analisis regresi menunjukkan teknik PS cenderung memiliki ROM lebih rendah dibandingkan CR (6-7° untuk fleksi lutut), namun secara statistik tidak bermakna. Usia pasien memiliki hubungan negatif yang bermakna dengan ROM pasca TKR. Simpulan penelitian ini ialah teknik CR dan PS memberikan hasil ROM yang ekuivalen pada pasien pasca TKR. Pemilihan teknik dapat disesuaikan dengan keahlian operator, ketersediaan implan, dan fasilitas rumah sakit. Penelitian lanjutan dengan durasi lebih panjang dan multi-senter diperlukan untuk mengevaluasi hasil jangka panjang. Kata kunci: total knee replacement; cruciate retaining; posterior stabilized; range of movement